MMP2 and MMP7 at the invasive front of gastric cancer are not associated with mTOR expression - Bornschein, Jan; Seidel, Tina; Langner, Cosima; Link, Alexander; Wex, Thomas; Selgrad, Michael; Jechorek, Doerthe; Meyer, Frank; Bird-Lieberman, Elizabeth; Vieth, Michael; Malfertheiner, Peter (Diagnostic Pathology, 2015)
Background: Regulation of MMP expression by activation of mTOR signalling has been demonstrated for several tumor types, but has thus far not been confirmed in gastric cancer. Findings: The study compromised 128 patients who underwent gastric resection for cancer (66.4 % male; 86 intestinal, 42 diffuse type). Immunohistochemical staining of MMPs was performed to analyse the topographical pattern of MMP expression at the tumor center and the invasive front, respectively. MMP2 showed higher expression at the invasive front compared to the tumor center, whereas MMP7 staining scores were higher in the tumor center, and there was no difference for MMP9. The expression of p-mTOR was higher in the tumor center than at the invasive front, with a similar trend for mTOR. For intestinal type gastric cancer there was a weak correlation of MMP9 with expression of mTOR in the tumor center. Otherwise, there was no correlation of the MMPs with mTOR. By treatment of MKN45 gastric cancer cells with rapamycin, a reduction of p-mTOR in the Western blot was achieved; however, expression of MMPs remained unaffected. Conclusions: Expression of MMP2 and MMP7 in gastric cancer is not associated with mTOR, MMP9 expression might be related to mTOR signalling in a subset of tumors.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Gastric cancer; MMP2; MMP7; MMP9; MTOR